To shuffle or not to shuffle - Barnes, C.; Hopker, J.; Gibson, S. (Journal of Science and Cycling, 2023)
The impact of a rider shuffling on their saddle is an issue that is often debated within the cycling fraternity. However, there are limited experimental results that support or refute the commonly held belief that shuffling might adversely affect a rider`s aerodynamic drag or power output. Indeed, when shuffling is investigated the primary focus of the research is often optimising rider position from a comfort perspective (Brooke & Broadbent, 2020). From a biomechanical perspective, when a rider moves forward on the saddle their affective saddle height decreases impacting on lower limb kinematics and ultimately reducing cycling efficiency (Ferrer-Roca et al., 2014), pedalling resultant force and force effectiveness (Bini et al., 2011). Therefore, it is hypothesised that cycling power output will be reduced in instances where riders have a high rate of shuffle.